LEVKO LUKIANENKO: A SIGNIFICANT LEADER IN THE HISTORY OF UKRAINIAN DISSENTENCE AND THE STRUGGLE FOR INDEPENDENCE - Шепілов, Гліб (SWorldJournal, 2024)
The work examines the prerequisites and main stages of the life path of Levko Lukyanenko, a Ukrainian human rights defender, politician and one of the leaders of the national liberation movement under Soviet totalitarianism. The peculiarities of his activ